Ceiba pentandra ethyl acetate extract improves doxorubicin antitumor outcomes against chemically induced liver cancer in rat model: a study supported by UHPLC-Q-TOF-MS/MS identification of the bioactive phytomolecules - Orabi, Mohamed A. A.; Abouelela, Mohamed E.; Darwish, Faten M. M.; Abdelkader, Mohamed S. A.; Elsadek, Bakheet E. M.; Al Awadh, Ahmed Abdullah; Alshahrani, Mohammed Merae; Alhasaniah, Abdulaziz Hassan; Aldabaan, Nayef; Abdelhamid, Reda A. (Frontiers in Pharmacology, 2024)
Hepatocellular carcinoma (HCC) is a prevalent cancer worldwide. Late-stage detection, ineffective treatments, and tumor recurrence contribute to the low survival rate of the HCC. Conventional chemotherapeutic drugs, like doxorubicin (DOX), are associated with severe side effects, limited effectiveness, and tumor resistance. To improve therapeutic outcomes and minimize these drawbacks, combination therapy with natural drugs is being researched. Herein, we assessed the antitumor efficacy of Ceiba pentandra ethyl acetate extract alone and in combination with DOX against diethylnitrosamine (DENA)-induced HCC in rats. Our in vivo study significantly revealed improvement in the liver-function biochemical markers (ALT, AST, GGT, and ALP), the tumor marker (AFP-L3), and the histopathological features of the treated groups. A UHPLC-Q-TOF-MS/MS analysis of the Ceiba pentandra ethyl acetate extract enabled the identification of fifty phytomolecules. Among these are the dietary flavonoids known to have anticancer, anti-inflammatory, and antioxidant qualities: protocatechuic acid, procyanidin B2, epicatechin, rutin, quercitrin, quercetin, kaempferol, naringenin, and apigenin. Our findings highlight C. pentandra as an affordable source of phytochemicals with possible chemosensitizing effects, which could be an intriguing candidate for the development of liver cancer therapy, particularly in combination with chemotherapeutic drugs.